Band gap engineering of In2O3 by alloying with Tl2O3 - WATSON, GRAEME (My University, 2013)
Efficient modulation of the bandgap of In 2 O 3 will open up a route to improved electronic properties. We demonstrate using ab initio calculations that Tl incorporation into In 2 O 3 reduces the band gap and confirm that narrowing of the gap is observed by X-ray photoemission spectroscopy on ceramic surfaces. Incorporation of Tl does not break the symmetry of the allowed optical transitions, meaning that the doped thin films should retain optical transparency in the visible region, in combination with a lowering of the conduction band effective mass. We propose that Tl-doping may be an efficient way to increase the dopability and carrier mobility of In 2 O 3
PUBLISHED
Keywords: Physics